Copper(II) Complexes of 1-Alkylamidino-O-alkylurea (alkyl=methyl or ethyl) and Its Growth Inhibition Activity Against Ceratocystis paradoxa - Rajen Singh, N.; Sudhesh Kumar Singh, Kh.; Linthoingambi, Ng.; Damayanti, M.; Hemakumar Singh, R.K.; Kadam, R.M. (Asian Journal of Chemistry, 2010)
Copper(II) complexes of the type [Cu(1-AAAUH)2]X2 where 1-AAAUH = 1-alkylamidino-O-alkylurea, X = Cl, Br, I, have been synthesized and characterized by elemental analyses, magnetic moments, electronic absorption, IR and EPR spectroscopy. EPR spectra of two complexes [Cu(II)(1-methylamidino-O-methylurea)2]Cl2 and [Cu(II)(1- ethylamidino- O-methylurea)2]Cl2 were recorded in solid state and in DMF and bonding parameters α2, β2 and γ2 were calculated. The orbital factors KII and K⊥ were also calculated. The trend KII < K⊥ indicates the presence of significant in plane π-bonding. The bis(1-alkylamidino-O-alkylurea)copper(II) complexes show growth inhibitory against pathogenic fungus Ceratocystis paradoxa.